Distinct mechanisms of allopregnanolone and diazepam underlie neuronal oscillations and differential antidepressant effect - Takasu, Keiko; Yawata, Yosuke; Tashima, Ryoichi; Aritomi, Hiroyuki; Shimada, Shinji; Onodera, Tsukasa; Taishi, Teruhiko; Ogawa, Koichi (Frontiers in Cellular Neuroscience, 2024)
Rapid relief of depressive symptoms is a major medical need in effective treatments for major depressive disorder (MDD). A decrease in neuroactive steroids contributes to the pathophysiological mechanisms associated with the neurological symptoms in MDD. Zuranolone (SAGE-217), a neuroactive steroid that acts as a positive allosteric modulator of synaptic and extrasynaptic -subunitcontaining GABAA receptors, has shown rapid-onset, clinically effective antidepressant action in patients with MDD or postpartum depression (PPD). Benzodiazepines, on the other hand, act as positive allosteric modulators of synaptic GABAA receptors but are not approved for the treatment of patients with MDD. It remains unclear how differences in molecular mechanisms contribute to the alleviation of depressive symptoms and the regulation of associated neuronal activity. Focusing on the antidepressant-like effects and neuronal activity of the basolateral amygdala (BLA) and medial prefrontal cortex (mPFC), we conducted a head-to-head comparison study of the neuroactive steroid allopregnanolone and the benzodiazepine diazepam using a mouse social defeat stress (SDS) model.Allopregnanolone but not diazepam exhibited antidepressant-like effects in a social interaction test in SDS mice. This antidepressant-like effect of allopregnanolone was abolished in extrasynaptic GABAA receptor -subunit knockout mice ( mice) subjected to the same SDS protocol. Regarding the neurophysiological mechanism associated with these antidepressant-like effects, allopregnanolone but not diazepam increased theta oscillation in the BLA of SDS mice. This increase did not occur in  mice. Consistent with this, allopregnanolone potentiated tonic inhibition in BLA interneurons via -subunit-containing extrasynaptic GABAA receptors. Theta oscillation in the mPFC of SDS mice was also increased by allopregnanolone but not by diazepam. Finally, allopregnanolone but not diazepam increased frontal theta activity in electroencephalography recordings in naïve and SDS mice.Neuronal network alterations associated with MDD showed decreased frontal theta and beta activity in depressed SDS mice. These results demonstrated that, unlike benzodiazepines, neuroactive steroids increased theta oscillation in the BLA and mPFC through the activation of -subunit-containing GABAA receptors, and this change was associated with antidepressant-like effects in the SDS model.Our findings support the notion that the distinctive mechanism of neuroactive steroids may contribute to the rapid antidepressant effects in MDD.